General anesthesia exposure in early life reduces the risk of allergic diseases: A nationwide population-based cohort study. Issue 28 (July 2016) - Kuo, Ho-Chang; Yang, Ya-Ling; Ho, Shu-Chen; Guo, Mindy Ming-Huey; Jiang, Jyun-Hong; Huang, Ying-Hsien
Abstract : Abstract: General anesthesia (GA) has been used for second line treatment strategy for status asthmaticus in pediatric patients. The association between GA in children and risk of followed-up allergic diseases is unclear. This study aims to assess the risk of allergic diseases after GA in children. We did a nationwide retrospective cohort study by analyzing data from the National Health Insurance Research Database (NHIRD) in Taiwan. The subsequent risks for allergic diseases, including asthma (ICD-9: 493.X), allergic rhinitis (AR; ICD-9 CM code 477.X), and atopic dermatitis (AD; ICD-9-CM code 691.X), were compared between exposure to GA and none before 1 year of age throughout the follow-up period using the Cox proportional hazards model. Insurance claims data for 32, 742 children younger than 1 year old from all insured children in the NHIRD. Of those, 2358 subjects were exposed to GA; 414 and 1944 children exposed to mask and intubation ventilation, respectively, served as the study cohort, whereas the remaining 30, 384 children made up the comparison cohort. Children in the GA group were at a lower risk of developing asthma, AR and AD, with adjusted hazard ratios of 0.67 (0.62–0.72, 95%CI), 0.72 (0.68–0.77, 95%CI), 0.60 (0.56–0.64, 95%CI), respectively. Children who were exposed to GA in early life before 1 year of age had reduced risk of subsequently developing allergic diseases such as asthma, AD, and AR, when compared with general population.